PENGARUH KELEBIHAN PENUMPANG TERHADAP STOWAWAY DI ATAS KAPAL KM SIRIMAU - Sitti Ananda Triana Syafitri; Faisal Saransi; Abdul Wahid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
As an archipelagic country, Indonesia relies heavily on maritime transportation to support inter-island connectivity, community mobility, and the distribution of goods. However, several challenges remain in maritime transportation, one of which is passenger overcapacity, which has the potential to increase the occurrence of stowaways. This condition may adversely affect maritime safety and security. This study aims to analyze the effect of passenger overcapacity on the occurrence of stowaways aboard KM Sirimau. A quantitative approach was employed, with data collected through questionnaires distributed to 100 respondents. The data were analyzed using the Pearson Chi-Square test to examine the relationship between the variables, while the strength of the relationship was measured using the Phi coefficient and Cramer's V. The results revealed a Pearson Chi-Square value of 93.893 with a significance level of less than 0.001, indicating a statistically significant relationship between passenger overcapacity and the presence of stowaways. Furthermore, the Phi and Cramer's V coefficients were both 0.916, indicating a very strong association between the two variables. These findings suggest that an increase in passenger overcapacity is associated with a higher likelihood of stowaway incidents. Therefore, stricter supervision of passenger capacity, thorough identity verification, and the effective implementation of security procedures are essential to enhance maritime safety and security aboard KM Sirimau.